Analisis Prinsip Kerja Sama dalam Percakapan Siswa-Siswi SMA Budi Bakti: Kajian Pragmatik - Agustina Wora; Kukuh Elyana (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2026)
Effective communication requires the application of the cooperative principle to ensure that messages are conveyed accurately. However, compliance with and violations of this principle are still found in interactions among students. This study aims to describe the forms of compliance with and violations of the cooperative principle, analyze the factors causing these violations, and explain their pragmatic functions in conversations among students at SMA Budi Bakti. This study employed a descriptive qualitative approach using spoken utterances collected through observation, non-participatory observation, and audio recordings. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed 41 utterances, consisting of 23 instances of compliance and 18 instances of violations of the maxims of quantity, quality, relevance, and manner. Compliance was most frequently found in the maxim of quantity, while violations were most common in the maxim of manner. These violations were influenced by limited topic understanding, low self-confidence, the intention to create humor or intimacy, limited language proficiency, and social relationships among participants. The findings indicate that violations of the cooperative principle do not always reflect communication failure but may serve as meaningful communication strategies in student interactions.